2019
DOI: 10.2135/cropsci2018.09.0559
|View full text |Cite
|
Sign up to set email alerts
|

Population Structure and Genome‐Wide Association Analysis of Bruchid Resistance in Ethiopian Common Bean Genotypes

Abstract: The common bean (Phaseolus vulgaris L.) is among the most important grain legume crops in Africa. However, the common bean grain is heavily damaged by the Mexican bean weevil (Zabrotes subfasciatus Boheman). This study was conducted to determine the population structure and genome‐wide marker–trait associations of bruchid resistance in the common bean. The phenotypic diversity and population structure of 297 genotypes were analyzed, using the Illumina BARCBean6K_3 SNP BeadChip. The genotypes consisted of landr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 117 publications
(130 reference statements)
3
25
0
Order By: Relevance
“…The STRUCTURE software was set at burnin period length of 50,000 and after burn-in 50,000 Markov chain Monte Carlo (MMC) repetition were set ve times. For joint inference of population substructure, the kinship (K) set at the range of 1 to 10 with ve number of iterations runs for each (Kamfwa et al, 2015a;Tigist et al, 2019). The ideal number of sub-populations was determined using K method [57] implemented in the HARVESTER software [58].…”
Section: Population Structure Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The STRUCTURE software was set at burnin period length of 50,000 and after burn-in 50,000 Markov chain Monte Carlo (MMC) repetition were set ve times. For joint inference of population substructure, the kinship (K) set at the range of 1 to 10 with ve number of iterations runs for each (Kamfwa et al, 2015a;Tigist et al, 2019). The ideal number of sub-populations was determined using K method [57] implemented in the HARVESTER software [58].…”
Section: Population Structure Analysismentioning
confidence: 99%
“…Genome-wide association study (GWAS) has been used to determine genomic variants associated with traits of interest using recombinant inbreed line population or landraces population [15], [16]. Literatures have demonstrated that some genomic regions have been identi ed to be associated with traits, such as bruchid resistance [17], cooking time of andean diversity panel [18], agronomic traits [19], drought tolerance [20], anthracnose and angular leaf spot diseases [21] and symbiotic nitrogen xation [22] in common bean. However, there is a limited information on grain micronutrient contents of Fe and Zn as well as seed water imbibition during pre-soaking and cooking time.…”
Section: Introductionmentioning
confidence: 99%
“…Various candidate genes or quantitative trait loci responsible for traits of interest have been identi ed using GWAS technology in different crops. For instance, in common bean several studies have reported identi cation of genomic regions and candidate genes associated with different traits for bruchid resistance [11], agronomic traits [12], drought tolerance [13], anthracnose and angular leaf spot diseases [14] and symbiotic nitrogen xation [15]. However, these studies have been conducted for different traits with different common bean cultivars in different geographical regions.…”
Section: Introductionmentioning
confidence: 99%
“…Various candidate genes or quantitative trait loci responsible for traits of interest have been identi ed using GWAS technology in different crops. For instance, in common bean several studies have reported identi cation of genomic regions and candidate genes associated with different traits for bruchid resistance [21], agronomic traits [22], drought tolerance [23], anthracnose, angular leaf spot and Fusarium wilt diseases [24,25] and symbiotic nitrogen xation [26]. However, these studies have been conducted for different traits with different common bean cultivars in different geographical regions.…”
Section: Introductionmentioning
confidence: 99%